POLYMORPHISM ANALYSIS OF HENAN FAT-TAILED SHEEP USING MICROSATELLITE MARKERS - J. Y. Bai; X. P. Jia; Y. B. Yang; X. H. Zhang; Y. Z. Pang; Y. Q. Wang; Y. X. Qi (Journal of Animal and Plant Sciences, 2014)
Five microsatellite markers were selected for studying the DNA polymorphism of fat-tailed sheep, aiming to understand the genetic diversity of this species. The genetic diversity of five microsatellite markers (BL1038, BM757, BM4621, OarFCB304 and OarFCB48) in fat-tailed sheep population was detected through the native polyacrylamide gel electrophoresis. The results indicated that fat-tailed sheep population has 68 alleles in these five microsatellite markers and its effective number of alleles was 7.7352-13.0962. The average effective number of alleles (Ne) of these five microsatellite markers was 8.9896, among which OarFCB48 has the highest Ne (13.0962). The average heterozygosity of these five microsatellite markers valued 0.8840, among which OarFCB48 achieved the highest heterozygosity (0.9236), which has also the highest PIC content (0.9187), while BM757 achieved the lowest PIC content (0.8571).The average PIC valued 0.8749 in this study. This indicated that the studied fat-tailed sheep population belongs to the genetic population with higher polymorphism information content. Furthermore, the fat-tailed sheep can be bred purely and selectively further to increase the uniformity of the population.
Keywords: Henan Fat-tailed sheep; Microsatellite marker; Genetic diversity